IIUM press customer survey 2011: perception and satisfaction - Wok, Saodah (s.n, 2012)
Customer satisfaction is one of the factors influencing customers loyalty to certain organization (Ranjbarian, Dabestani, Khajed & Noktehden, 2001). Therefore a study on the assessment and feedback from customers to ascertain that the products and services offered by the organization are well received needs to be carried out. This is important so that improvement can be made accordingly to tailor to the needs of the customers (Abraham, 2010)